The abandoned empress. 7 - In-a; Yuna (Yen Press, 2024)
"IT WAS THE SOUND OF THE GODS SCOFFING AT ME." Thanks to Ruveliss's decisive actions, the foreign princesses' schemes are thwarted, but this was merely a prelude to the oncoming turmoil. With the emperor's health waning, political machinations at the court intensify...and at the center of it all stands Aristia. To make matters worse, Carsein suffers a grave injury while protecting her from mysterious assassins, and the shadow inside Allendis's heart continues to grow. With crisis after crisis erupting all around her, Tia finds herself relying more and more on Ruveliss for support. ...All the while, the cogs of fate spin ever forward, indifferent to the struggles of mortals--until the gears click into place at the destined hour...Jieun has arrived.